2017
DOI: 10.1007/s00264-017-3430-5
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein may misdiagnose prosthetic joint infections, particularly chronic and low-grade infections

Abstract: Per the American Association of Orthopaedic Surgeons (AAOS) guidelines or the Musculoskeletal Infection Society (MSIS), 23% of the patients in the present study with PJI would never have been identified. Blood inflammatory markers such as the CRP level and ESR may not be accurate as diagnostic tools in PJI, particularly to identify low-grade and chronic PJI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 26 publications
2
88
1
5
Order By: Relevance
“…However, CRP and ESR are inflammatory markers with a low sensitivity: levels within the normal range do not rule out infection. Pérez-Prieto et al [23] found that one third of PJI presented normal CRP levels and that approximately two thirds of these also had a normal ESR, and Akgün et al [24] had similar findings. This is the case especially in low-grade infections due to coagulase-negative staphylococci and Cutibacterium spp.…”
Section: Use Of Swab Samplesmentioning
confidence: 86%
“…However, CRP and ESR are inflammatory markers with a low sensitivity: levels within the normal range do not rule out infection. Pérez-Prieto et al [23] found that one third of PJI presented normal CRP levels and that approximately two thirds of these also had a normal ESR, and Akgün et al [24] had similar findings. This is the case especially in low-grade infections due to coagulase-negative staphylococci and Cutibacterium spp.…”
Section: Use Of Swab Samplesmentioning
confidence: 86%
“…CRP has been considered as a specific indicator for the diagnosis of PJI, and its diagnostic sensitivity and specificity are similar to that of histopathology [39], which has also been recommended in guidelines [40]. P erez-Prieto et al [41] had revealed that CRP lacks sensitivity in detecting PJI, especially in low-grade and chronic cases. Patients included in this study were diagnosed with chronic PJI, and it was found that CRP had a sensitivity of 81.13% and specificity of 65.67%, indicating the limited diagnostic value of CRP in chronic PJI.…”
Section: Discussionmentioning
confidence: 99%
“…However, CRP is not specific for infection and usually increases due to healing process after intervention. Pérez-Prieto et al18) found that with normal CRP about one-third of chronic, low-grade infections would be missed. So the combination of CRP and ESR is used for diagnose PJI1920), the sensitivity of combined ESR (>30 mm/hr) and CRP (>10 mg/L) was 96%, but low specificity 56%21).…”
Section: Diagnosismentioning
confidence: 99%